L’apprentissage par le service en langues: innovation et mise en application - Olmo-Cazevieille, Françoise (Didáctica. Lengua y Literatura, 2022)
This article presents the implementation of service-learning projects in a foreign language classroom. This methodology makes it possible to develop the pursued objectives: the acquisition of scientific and technical French language in the field studied, the development of transversal skills and civic engagement. Firstly, the concept, its origin, its definitions and the scientific model to be followed are examined. Secondly, the implementation of projects led by B1 level engineering students is developed. They create simple and useful products for the Burkinabe to help them in their daily life. The results of an individual questionnaire on the activity carried out reveal the students’ perceptions. Teamwork not only allows them to create links between their academic learning and the everyday world, but also to act as world citizens and thus prepare themselves for their professional future.